Investigating University Student’s Acceptance of Moodle - Nasution, Nanda Eska Anugrah (META: Journal of Science and Technological Education, 2024)
The Indonesian government has temporarily closed higher educational institutions across the country and changed the learning activity to distance learning to prevent further spread of coronavirus disease 2019 (COVID-19). Various universities, including the State Islamic Institute of Jember, try to adopt Moodle as a learning management system during this COVID-19 pandemics situation. This study aims to take TAM (technology acceptance model) as a basic and include prior experience, enjoyment, facilitating conditions, self-efficacy, and subjective norm as a new external variable in predicting students’ acceptance and use of Moodle. SPSS 25.0 was used for the quantitative analysis. Data collected were analyzed using descriptive statistics of Mean and Standard Deviation. Multiple regression analysis was conducted to test the hypothesis of structure model. A total of 217 college students were involved in this study. These students had been using Moodle for at least six months. The results of this study confirm the original TAM’s findings and reveal that the Moodle was well accepted. Prior experience, enjoyment, facilitating conditions, self-efficacy, and subjective norm had significantly positive impacts on students’ perception of usefulness and perception ease of use.